ChemInform Abstract: A Hexanuclear Cobalt(II) Cluster Incorporated in a Banana‐Shaped Tungstovanadate: [(Co(OH2)Co2VW9O34)2 (VW6O26)]17‐. Issue 47 (4th November 2013) - Lv, Hongjin; Song, Jie; Geletii, Yurii V.; Guo, Weiwei; Bacsa, John; Hill, Craig L.
Abstract Na17 [(Co(OH2)Co2VW9O34)2 (VW6O26)]·31H2O (I) is synthesized from Na2WO4, Co(NO3)2, and V2O5 in acetate buffer solution (pH 4.8, 80 °C, 2 h, 24% yield).